Computer-Assisted Collaborative Learning and Academic Performance - Estimo, Emeliza T. (JPAIR Multidisciplinary Research, 2012)
For the continuing search for effective teaching methodology in Maritime English Instruction, this paper examines the effect of the Computer-Assisted Collaborative Learning (CACL) Method on the academic performance of maritime students in terms of their scores in the summative test, pretest and post test, and midterm examination. The study used the experimental design. A series of CACL-based modules covering the midterm topics which was enriched from the existing Instructor’s Guide for Maritime English was tested with two experimental groups of students against two other classes who were exposed to the Traditional Method (TM) of instruction. The four groups of students were categorized into academic achievers and non-academic achievers. Findings revealed a significant improvement on the academic performance of all groups after their separate exposure to the two methods. Results from the midterm exam and the summative test further revealed that there is no significant difference on the academic performance of the groups of academically advanced students. For the groups of non-achievers, however, those who were exposed to the CACL method had significantly scored higher than those who were taught using the Traditional Method.